(untitled) (Journal of Asian Development Studies, 2024)
William Shakespeare is famous for the universality and uniqueness of his plays. Most of the characters that he portrays are life-like. In most of his plays, he portrays some manipulative characters who cunningly ruin the lives of the people around them. People trust, love, and admire them, but in response, these manipulative persons exploit them to achieve their goals. Othello (1603) and King Lear (1605) are two different tragic plays written by Shakespeare, and both have manipulative characters, i.e., Iago in Othello and Edmond in King Lear. They have been analyzed in this study to discover Shakespeare’s understanding of human nature as manipulative in society and the meaningful similarities between them in light of the comparative contextual analysis technique. The findings reveal Shakespeare’s nuanced portrayal of manipulative characters, showcasing the parallel yet distinct paths taken by Iago in "Othello" and Edmund in "King Lear," highlighting their cunning tactics, societal impact, and the universal thread of human manipulation; the conclusion underscores Shakespeare’s profound comprehension of the darker facets of human nature, depicting the intricate interplay of manipulation, trust, and societal influence within his tragic plays